Metasurfaces: Enhancement of Magnetic Resonance Imaging with Metasurfaces (Adv. Mater. 9/2016). Issue 9 (1st March 2016) - Slobozhanyuk, Alexey P.; Poddubny, Alexander N.; Raaijmakers, Alexander J. E.; van den Berg, Cornelis A. T.; Kozachenko, Alexander V.; Dubrovina, Irina A.; Melchakova, Irina V.; Kivshar, Yuri S.; Belov, Pavel A.
Abstract : On page 1832, A. P. Slobozhanyuk and co‐workers report the unique properties of an ultrathin metasurface resonator that can dramatically improve magnetic resonance imaging (MRI) characteristics. The placement of the metasurface, formed by an array of metallic wires, inside the scanner under a studied biological object results in a giant improvement of the scanner sensitivity and image resolution. Image design by Anna Zubkova and Alexey Slobozhanyuk.